Smuggling of Rohingyas from Myanmar to Malaysia: a threat to human security - Andika Ab Wahab,; Aizat Khairi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Irregular migration of the Rohingyas from Myanmar to Malaysia has been made possible by the presence of smuggling networks, which activities are not well understood due to their clandestine and complex modus operandi. Althoughthe smuggling of Rohingyas can help to ensure their safe migration to Malaysia, it is also associated with a variety of risks and threats against the Rohingya victims. This study seeks to describe the smuggling of Rohingyas from Myanmar to Malaysia and aims to explain how their smuggling becomes a threat to their human security. Deriving from a two-part field work engaging the Rohingya refugees, activists and community leaders between 2013 and 2016 in Klang Valley, Malaysia, this studyfound that the smuggling of Rohingyas consists of several typical activities such as recruitment of victims, negotiating the terms of their smuggling, embarkation from points of origin, and transiting in transit countries before their arrival in Malaysia. While some Rohingya victims managed to be smuggled without encountering any unfortunate incidents, other victims were exploited, deceived, coerced and physically assaulted and/or tortured throughout their smuggling journey. These extreme incidents depict that their smuggling can turn into another humanitarian crime, namelyhuman trafficking, and most importantly, puts their lives at greater risk of human (in) security. This studyfurther argues that the risks and threats facing by Rohingya victims are interlinked to one another. As such, any effort to eliminate the smuggling of Rohingyas should address the root causes including ensuring their full enjoyment of human rights and guaranteeing their safety and protection in Myanmar.